Maternal Health Care in Rural Uganda : Leveraging Traditional and Modern Knowledge Systems - Musoke, Maria G.N. (World Bank, Washington, DC, 2012)
This note reviews the Rural Extended Services and Care for Ultimate Emergency Relief (RESCUER) project in Uganda, started as an initiative to address strategies for expanding the maternal referral system, and improving the Traditional Birth Attendants (ABE) assistance. The project design addressed the high maternal mortality problem, which was implemented by a multi-sectoral Iganga district task force, and supported by an overall monitoring, implemented by the Ministry of Health, and the United Nations Fund for Population Activities (UNFPA). Lessons highlight how the mutual exclusive aspects of communication, transportation, and quality of services delivery, did however promote a successful interaction; how the impact of technology, appropriately considered the local problems, and conditions in Uganda; and, how institutional capacity, built on existing infrastructure, and local capacity, adequately included the traditional knowledge systems.